2018
DOI: 10.1177/1099800418779460
|View full text |Cite
|
Sign up to set email alerts
|

Eating Behavior, Stress, and Adiposity: Discordance Between Perception and Physiology

Abstract: The purpose of the study was to examine the interrelationships among stress, eating behavior, and adiposity in a cohort of normal- and overweight individuals. Clinical markers of physiological stress (fasting serum cortisol) and adiposity (body mass index [BMI] and percent body fat) were obtained from participants selected for a natural history protocol ( n = 107). Self-reported data on eating behavior (using the Three-Factor Eating Questionnaire subscales such as Cognitive Restraint, Disinhibition, and Hunger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 59 publications
1
23
0
1
Order By: Relevance
“…Similarly, it has been reported that FMS patients tend to experience high levels of stress (Galvez-Sánchez et al, 2019), and since pain and stress share significant conceptual and physiological overlaps (Abdallah & Geha, 2017), it should be of special interest to perform research that relates stress to diet in FMS patients. Previous studies have reported significant relationships between stress measures and eating behavior (Debeuf et al, 2018;Joseph et al, 2018) but, to the best of our knowledge, it has not been investigated in FMS patients. Finally, a further limitation is the lack of assessment of physical activity in these patients.…”
Section: Discussionmentioning
confidence: 88%
“…Similarly, it has been reported that FMS patients tend to experience high levels of stress (Galvez-Sánchez et al, 2019), and since pain and stress share significant conceptual and physiological overlaps (Abdallah & Geha, 2017), it should be of special interest to perform research that relates stress to diet in FMS patients. Previous studies have reported significant relationships between stress measures and eating behavior (Debeuf et al, 2018;Joseph et al, 2018) but, to the best of our knowledge, it has not been investigated in FMS patients. Finally, a further limitation is the lack of assessment of physical activity in these patients.…”
Section: Discussionmentioning
confidence: 88%
“…In another study, lower job control, which is present in job strain and in passive job, was associated with binge eating (1) , possibly because of the feeling of tension/anxiety generated (3) , which in turn may lead to a greater tendency to consume sweets and foods rich in saturated fat instead of healthier foods, such as fruits and vegetables (34) . Moreover, high cortisol levels (35) and hormonal imbalances involving leptin and ghrelin (36) observed in stressed individuals could be implicated in the pathophysiological mechanisms behind the reduction in the frequencies of fruit consumption over time associated with job strain. Last, a lack of time is a frequent complaint related to job strain and has been reported to be one of the reasons for not engaging in healthy behaviours, such as healthy eating (37) .…”
Section: Discussionmentioning
confidence: 99%
“…La percepción de estrés psicológico, la sintomatología depresiva y la ansiedad son variables que se han vinculado a múltiples comportamientos en salud, entre los cuales destaca la preferencia por alimentos no saludables Gibson-Smith et al, 2018;Joseph et al, 2018). En relación al estrés psicológico, se ha demostrado en forma experimental que ante la generación de alto estrés psicológico, los individuos prefieren alimentos ricos en contenido graso y calórico, por sobre comidas saludables y bajas en grasa (Tomiyama et al, 2015).…”
Section: Afectividad Negativa Y La Calidad De La Dietaunclassified